SPIRITUAL SCOUTCRAFT: METHODS DEPLOYED FOR RELIGIOUS CHARACTER VALUES INTEGRATION AT PONTIANAK'S ISLAMIC-BASED ELEMENTARY SCHOOLS - Erinda, Hayyu; Imron, Ali; Sunarni, Sunarni (Universitas Tanjungpura, 2024)
This research explores methods for integrating religious values in scouting, focusing on interaction dynamics, challenges, and solutions at SDIT Al-Mumtaz. Using a case study and qualitative methods (Miles, M.B, Huberman, A.M, Saldana, 2014), it condenses data stages, emphasizing diverse tailored methods aligned with scouting levels, integration goals, and student needs. Collaborative mentor efforts, flexibility, and adaptability are crucial. Intensive participant-facilitator interaction significantly impacts religious character values implementation. Facilitators, as